Catalytic Enantioselective Allylic Amination of Olefins for the Synthesis of ent-Sitagliptin - Bao, Hongli; Bayeh, Liela; Tambar, Uttam K. (Synlett, 2013)
The presence of nitrogen atoms in most chiral pharmaceutical drugs has motivated the development of numerous strategies for the synthesis of enantiomerically enriched amines. Current methods are based on multistep transformations of functionalized allylic electrophiles to form chiral allylic amines. The enantioselective allylic amination of nonactivated olefins would represent a more direct and more attractive strategy. We report the enantioselective synthesis of ent-sitagliptin through an allylic amination of a nonactivated terminal olefin.
Keywords: asymmetric catalysis; aminations; drugs; rearrangements; palladium